2011
DOI: 10.1017/s1463423611000533
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led case management in the National Health Service: bridging clinical and social worlds

Abstract: The opinions of older people receiving nurse case management reveal the value of high intensity support to individuals with major health and social needs. The NCMs' clinical expertise, the improved continuity of care they provided and the psychosocial support they offered, were all emphasised by older people or their carers. NCMs substituted for social workers in some cases, when the older person would not have been eligible for publicly funded social care or had declined it. In other cases, they supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The role of nurses as coordinators of complex care remains the subject of debate and contemporary research. For example, Manthorpe and colleagues (2012) identified that it is both the clinical expertise and the social support that nurses provide, which allows them to coordinate effective care. This analysis of nurse navigator vignettes has supported this view, identifying what Parker et al (2013, p. 38) term ‘understandings of nurses, link[ing] to perceptions of the kinds of “tacit knowledge” they have that can be brought to their nursing role’.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nurses as coordinators of complex care remains the subject of debate and contemporary research. For example, Manthorpe and colleagues (2012) identified that it is both the clinical expertise and the social support that nurses provide, which allows them to coordinate effective care. This analysis of nurse navigator vignettes has supported this view, identifying what Parker et al (2013, p. 38) term ‘understandings of nurses, link[ing] to perceptions of the kinds of “tacit knowledge” they have that can be brought to their nursing role’.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative case study design (Yin 2003) was used to investigate different nurse case manager delivery models: community matrons, district nurses, nurse specialists, nurse practitioner. Patients reported that case management provided significant psycho-social support (Manthorpe et al 2012), but interviews with local stakeholders found scepticism about the ability of nurse case managers to reduce hospital admissions and concerns about the disruption to local services that accompanied the introduction of community matrons (Iliffe et al 2011). Commissioners now thinking about the reconfiguration of community nursing (to optimize efficiency and effectiveness) need evidence about the impact of community matrons, when compared with other nurses carrying out case management (Drennan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…99 Other literature concentrates on methods of service delivery such as integrated case management (as promoted in recent Best Practice Guidance, 'Delivering Care Closer to Home'). 100 An integrated case management approach might be beneficial to patients 101,102 and reduce costs. 103 However, potential benefits are likely to be contingent on, for instance, the context, leadership, management and previous methods of service delivery (e.g.…”
Section: Defining and Organising Intermediate Carementioning
confidence: 99%